Two-hit mouse model of heart failure with preserved ejection fraction combining diet-induced obesity and renin-mediated hypertension - Justin H. Berger; Yuji Shi; Timothy R. Matsuura; Kirill Batmanov; Xian Chen; Kelly Tam; Mackenzie Marshall; Richard Kue; Jiten Patel; Renee Taing; Russell Callaway; Joanna Griffin; et al. (Scientific Reports, 2025)
Abstract Heart failure with preserved ejection fraction (HFpEF) is increasingly common but its pathogenesis is poorly understood. The ability to assess genetic and pharmacologic interventions is hampered by the lack of robust preclinical mouse models of HFpEF. We developed a novel “two-hit” model, which combines obesity and insulin resistance with chronic pressure overload to recapitulate clinical features of HFpEF. C57Bl6/NJ mice fed a high-fat diet (HFD) for > 10 weeks were administered an AAV8-driven vector resulting in constitutive overexpression of mouse Renin1d. HFD-Renin (aka “HFpEF”) mice demonstrated obesity and insulin resistance, moderate left ventricular hypertrophy, preserved systolic function, and diastolic dysfunction indicated by echocardiographic measurements; increased left atrial mass; elevated natriuretic peptides; and exercise intolerance. Transcriptomic and metabolomic profiling of HFD-Renin myocardium demonstrated upregulation of pro-fibrotic pathways and downregulation of metabolic pathways, in particular branched chain amino acid catabolism, similar to human HFpEF. Treatment with empagliflozin, an effective but incompletely understood HFpEF therapy, improved multiple endpoints. The HFD-Renin mouse model recapitulates key features of human HFpEF and will enable studies dissecting the contribution of individual pathogenic drivers to this complex syndrome. Additional preclinical HFpEF models allow for orthogonal studies to increase validity in assessment of interventions.